2014
DOI: 10.1007/s12020-014-0309-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 expressions in white blood cells and sera of patients with gestational diabetes mellitus during gestation and postpartum

Abstract: Fibroblast growth factor 21 (FGF21), a recently discovered regulatory factor, plays an important role in glucose and lipid metabolism. In this study, we firstly found the FGF21 expression in white blood cells (WBCs). Then, we enrolled 51 women with gestational diabetes mellitus (GDM) and 50 pregnant women with normal blood glucose levels to determine the FGF21 levels in the WBCs and the sera at the 28th week of pregnancy, and tracked the dynamic changes of FGF21 in these women until the 7th day postpartum. Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…25 A similar study of 90 pregnant women of Chinese ethnicity also revealed that serum FGF21 levels were higher in patients with GDM (median: 125 pg/mL; IQR 83-190) compared to controls (median 68 pg/mL; IQR 49-98 pg/mL; P < 0.001). 25 A similar study of 90 pregnant women of Chinese ethnicity also revealed that serum FGF21 levels were higher in patients with GDM (median: 125 pg/mL; IQR 83-190) compared to controls (median 68 pg/mL; IQR 49-98 pg/mL; P < 0.001).…”
Section: Studies With a Significant Difference In Circulating Fgf21mentioning
confidence: 74%
See 4 more Smart Citations
“…25 A similar study of 90 pregnant women of Chinese ethnicity also revealed that serum FGF21 levels were higher in patients with GDM (median: 125 pg/mL; IQR 83-190) compared to controls (median 68 pg/mL; IQR 49-98 pg/mL; P < 0.001). 25 A similar study of 90 pregnant women of Chinese ethnicity also revealed that serum FGF21 levels were higher in patients with GDM (median: 125 pg/mL; IQR 83-190) compared to controls (median 68 pg/mL; IQR 49-98 pg/mL; P < 0.001).…”
Section: Studies With a Significant Difference In Circulating Fgf21mentioning
confidence: 74%
“…A study of 101 pregnant women of north-eastern Chinese ethnicity at the 28th week of gestation found significantly higher serum FGF21 levels among women with GDM than in controls matched for gestational age and weight (400 ± 128 ng/L vs 248 ± 107ng/L, P < 0.01). 25 A similar study of 90 pregnant women of Chinese ethnicity also revealed that serum FGF21 levels were higher in patients with GDM (median: 125 pg/mL; IQR 83-190) compared to controls (median 68 pg/mL; IQR 49-98 pg/mL; P < 0.001). 24 Based on previous studies on the role of FGF21 in different metabolic diseases with similar pathophysiological mechanisms to GDM, it can be speculated that this upregulation of FGF21 may be a compensatory mechanism for the underlying insulin resistance in order to increase whole-body F I G U R E 2 Mechanisms by which FGF21 improves glycaemic control in mouse and in vitro cell culture models.…”
Section: Studies With a Significant Difference In Circulating Fgf21mentioning
confidence: 74%
See 3 more Smart Citations